Does power predict emotional abuse in adolescent romantic relationships? - Qolbunnisa, Ghina; Anggarani, Fadjri Kirana (University of Muhammadiyah Malang, 2024)
The aim of the current study is to explore the association between power perception and emotional abuse, with power satisfaction as a mediating factor, and to determine the prevalence of reciprocal emotional abuse within adolescent romantic relationships. The sample consisted of 184 (15-18 years) in romantic relationships for at least six months and were students at SMAS A, SMKN B, and SMAN C, selected using a purposive sampling technique. Data were collected using the Multidimensional Measure of Emotional Abuse Scale and Power Perception and Power Satisfaction Scale. The scale reliability indicates good results, α ≥ 0.8 for MMEA dimensions and α > 0.66 for Power scale. Data were analyzed using the causal step method. The analysis results show that power perception, mediated by power satisfaction, does not significantly affect emotional abuse in adolescents (p > 0.05). In adolescents, the power perception tends to be the same, and they generally experience high power satisfaction. The research also shows that emotional abuse between adolescents with romantic relationships occurs reciprocally (p < 0.01; r > 0.194). The research results are expected to contribute to future studies and the design or development of interventions aimed at preventing emotional abuse in adolescent relationships.